Acute coronary syndrome as the first symptom of vasospastic angina – case report of a 38-year-old man with myocardial infarction with non-obstructive coronary artery disease - Łukasz Gabryel; Klaudyna Bugla; Tomasz Pawłowski; Aneta Gziut-Rudkowska (Annales Academiae Medicae Silesiensis)
A 38-year-old obese man with hypertension and a twenty-year history of nicotinism was admitted for a suspected ST-segment elevation myocardial infarction (STEMI). Coronary angiography did not reveal significant coronary artery stenosis, which, together with symptoms of acute coronary syndrome and increased troponin I levels, led to the diagnosis of myocardial infarction with non-obstructive coronary artery disease (MINOCA) and implied a differential diagnosis. Given the clinical picture, a provocative test with acetylcholine was performed, which indicated the vasoconstrictive origin of MINOCA. In order to reduce the likelihood of another episode, pharmacotherapy was changed and lifestyle changes were recommended.